2017
DOI: 10.1186/s12866-017-0949-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pathogenic and non-pathogenic Enterococcus cecorum strains from different animal species

Abstract: Background Enterococcus cecorum (EC) infection currently is one of the most important bacterial diseases of modern broiler chickens but can also affect ducks or other avian species. However, little is known concerning pathogenesis of EC and most studies concentrate on examinations of EC strains from broilers only. The objective of this study was to compare pathogenic and commensal EC strains from different animal species concerning different phenotypic and genotypic traits.ResultsPathogenic and commensal EC st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 41 publications
9
57
1
4
Order By: Relevance
“…A higher prevalence of gelE, asa1 and ace was in line with other studies concerning enterococci in farm animals [9,16] but not with the results for enterococci isolated from food-stuffs [26]. The lower detection rate of cylA and esp in racing pigeons was in near agreement with poultry isolates [9,16,27]. Incidences of esp detection in enterococci isolated from cattle and pigs were higher than in our study [16,27].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…A higher prevalence of gelE, asa1 and ace was in line with other studies concerning enterococci in farm animals [9,16] but not with the results for enterococci isolated from food-stuffs [26]. The lower detection rate of cylA and esp in racing pigeons was in near agreement with poultry isolates [9,16,27]. Incidences of esp detection in enterococci isolated from cattle and pigs were higher than in our study [16,27].…”
Section: Discussionsupporting
confidence: 80%
“…In this study we confirmed the presence of 6 different virulence genes in Enterococcus isolated from intestinal microbiota of racing pigeons. A higher prevalence of gelE, asa1 and ace was in line with other studies concerning enterococci in farm animals [9,16] but not with the results for enterococci isolated from food-stuffs [26]. The lower detection rate of cylA and esp in racing pigeons was in near agreement with poultry isolates [9,16,27].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations